Improvisation Matters: The Vision, Scholarship, and Legacy of Ajay Heble: A welcome from the editors of Critical Studies in Improvisation / Études critiques en improvisation

(untitled) (University of Guelph College of Arts, 2025)
In this special issue of Critical Studies in Improvisation / Études critiques en improvisation, the editors have compiled a collection of articles, artistic offerings, and personal reflections from colleagues, friends, collaborators, students, and community members whose lives have been impacted by Ajay Heble. Marking the occasion of Ajay Heble receiving Professor Emeritus status at the University of Guelph, this issue not only celebrates Ajay's ongoing legacy, but also provides an array of insights into the power of community work, the impact of innovative research methods, and the importance of heartfelt collaboration that connects academic and social spheres. What emerges in this issue is the fact that the relationships formed through community-based work academic research are a foundation of social change.